Boris Yeltsin and Russia's Democratic Transformation. - Ellison, Herbert J. (Jackson School publications in international studies., 2006)
Examines Boris Yeltsin's role as the principal leader and defender of Russia's democratic revolution, exploring how he fought to protect Russia's fragile new liberties, including the core freedoms of speech, religion, press, and political association.